2008
DOI: 10.1128/aem.02218-07
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Spatial and Temporal Patterns of Antimicrobial Action within Model Oral Biofilms

Abstract: A microscopic method for noninvasively visualizing the action of an antimicrobial agent inside a biofilm was developed and applied to describe spatial and temporal patterns of mouthrinse activity on model oral biofilms. Three species biofilms of Streptococcus oralis, Streptococcus gordonii, and Actinomyces naeslundii were grown in glass capillary flow cells. Bacterial cells were stained with the fluorogenic esterase substrate Calcien AM (CAM). Loss of green fluorescence upon exposure to an antimicrobial formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 38 publications
7
56
0
1
Order By: Relevance
“…However, in deep layers of oral biofilms not all bacteria were reached (49). Direct visualization by fluorescence microscopy of the CHX effect was described by Takenaka et al (44) for a three-species oral biofilm grown in vitro. Cell damage started from the periphery of bacterial aggregates and slowly continued into the depths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in deep layers of oral biofilms not all bacteria were reached (49). Direct visualization by fluorescence microscopy of the CHX effect was described by Takenaka et al (44) for a three-species oral biofilm grown in vitro. Cell damage started from the periphery of bacterial aggregates and slowly continued into the depths.…”
mentioning
confidence: 99%
“…Electron microscopic examinations showed that CHX binds to and damages bacterial cell membranes and leads to structural changes and leakage of cytoplasm (3). Furthermore, contraction of in vitro grown biofilms after CHX exposure was shown in addition to cell damage (19,44), which could cause changes in the diffusion behavior by changes to extracellular polymeric slime density. However, in deep layers of oral biofilms not all bacteria were reached (49).…”
mentioning
confidence: 99%
“…Fluorescence microscopy represents an essential and noninvasive method to assess antimicrobial dynamics and reactivity in biofilms, contributing to our understanding of what makes bacteria resistant in these biostructures (3,5,8,29). In this respect, confocal laser scanning microscopy (CLSM) has been shown to be a powerful tool to analyze antimicrobial actions indirectly by a time course (hour-to-day scale) visualization of live and dead cells through the biofilm structure (4,17,29,34).…”
mentioning
confidence: 99%
“…We performed a direct time-lapse microscopic observation throughout continuous exposure of commercial mouthrinses to an oral biofilm model [10]. Consequently, no removal of biomass was observed in control, ethanol (EtOH), 0.12% chlorhexidine gluconate (CHG), and Biotene, which contains lysozyme, lactoferrin, lactoperoxidase, glucose oxidase, and potassium thiocyanate, even after 20 min exposure.…”
Section: Residual Structurementioning
confidence: 99%